Early acquisition of sign language What neuroimaging data tell us - Malaia, Evie (2010)
Early acquisition of a natural language, signed or spoken, has been shown to fundamentally impact both one's ability to use the first language, and the ability to learn subsequent languages later in life (Mayberry 2007, 2009). This review summarizes a number of recent neuroimaging studies in order to detail the neural bases of sign language acquisition. The logic of this review is to present research reports that contribute to the bigger picture showing that people who acquire a natural language, spoken or signed, in the normal way possess specialized linguistic abilities and brain functions that are missing or deficient in people whose exposure to natural language is delayed or absent. Comparing the function of each brain region with regards to the processing of spoken and sign languages, we attempt to clarify the role each region plays in language processing in general, and to outline the challenges and remaining questions in understanding language processing in the brain.